Recent trends in technical education in Latin America - Jacinto, CLaudia (Policies and strategies for secondary education, 2010)
"This book examines recent transformations with regards to the links between academic secondary education (ASE), technical and vocational education and training (TVET), and job preparation skills, in the Latin America region. It analyses changes in approaches, obstacles and advances, and major challenges, and reviews some promising strategies."--www.iiep.unesco.org